THE IMPACT OF TRAINING QUALITY, MANAGERIAL SKILL AND SALES MOTIVATION ON DEVELOPING SALESMAN PERFORMANCE TO INCREASE SALES EFFECTIVENESS - Novita, Elvira; Soesanto, Harry; Sutopo, Sutopo (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2017)
The purpose of this research is to analyze the influences of training quality, managerial skill, sales motivation toward salesman performance to impact the salesman performance to increase sales effectiveness. The research problem is how to increase of training quality, managerial ability, sales motivation toward salesman performance to impact the sales effectiveness.This research analyzes the factor that influences repurchase intention use mediating variable brand preference.Â  This research developed a theoretical model by submitting four hypotheses where will be tested by Structural Equation Model (SEM) used AMOS 21.0. Respondents in this research are people who work as a credit card salesman with total 157 respondents.Â  The result of SEM data processing already found the goodness of fit follows, the value of chi-square = 77,261, df: 96, p:5%; probability = 0,920; GFI = 0,940; AGFI = 0,915; TLI = 1,013; CFI = 0,959; CMIN/DF = 0,805;RMSEA = 0,000. Empirical analyze indicate the influences of training quality are significant to salesman performance; the effect of sales motivation are significant to salesman performance; the effect of managerial skill are significant to salesman performance;the effect of salesman performance are significant to sales effectiveness and the effect of managerial skill are significant to sales effectiveness.Â